2001
DOI: 10.1055/s-2001-12428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GLP-1 on Lipid Metabolism in Human Adipocytes

Abstract: We have studied the effect of several doses of GLP-1, compared to that of insulin and glucagons, on lipogenesis, lipolysis and cAMP cellular content, in human adipocytes isolated from normal subjects. In human adipocytes, GLP-1 exerts a dual action, depending upon the dose, on lipid metabolism, being lipogenic at low concentrations of the peptide (ED50, 10(-12) M), and lipolytic only at doses 10-100 times higher (ED50, 10(-10) M); both effects are time- and GLP-1 concentration-dependent. The GLP-1 lipogenic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(48 citation statements)
references
References 21 publications
2
42
2
2
Order By: Relevance
“…However, in contrast to WAT, the effects of CNS GLP-1 on hepatic lipid deposition are dependent on and presumably secondary to reduced nutrient intake. Although GLP-1-R has not been found in WAT (Bullock et al, 1996), several studies have suggested that GLP-1 can directly act on adipocyte metabolism, although the molecular mechanisms modulating those peripheral actions are unknown (Ruiz-Grande et al, 1992;Mérida et al, 1993;Valverde et al, 1993;Bertin et al, 2001;Villanueva-Peñacarrillo et al, 2001;Sancho et al, 2005Sancho et al, , 2006. We have excluded the possibility that increased peripheral GLP-1 levels contributed to the observed effects, because peripheral infusion of the identical amount of GLP-1 failed to trigger any effects.…”
Section: Discussionmentioning
confidence: 84%
“…However, in contrast to WAT, the effects of CNS GLP-1 on hepatic lipid deposition are dependent on and presumably secondary to reduced nutrient intake. Although GLP-1-R has not been found in WAT (Bullock et al, 1996), several studies have suggested that GLP-1 can directly act on adipocyte metabolism, although the molecular mechanisms modulating those peripheral actions are unknown (Ruiz-Grande et al, 1992;Mérida et al, 1993;Valverde et al, 1993;Bertin et al, 2001;Villanueva-Peñacarrillo et al, 2001;Sancho et al, 2005Sancho et al, , 2006. We have excluded the possibility that increased peripheral GLP-1 levels contributed to the observed effects, because peripheral infusion of the identical amount of GLP-1 failed to trigger any effects.…”
Section: Discussionmentioning
confidence: 84%
“…Whereas ghrelin increases food intake (1,2), gastric acid secretion and motility (5), and fat deposition (1), GLP-1 reduces food intake (12,13), gastric acid secretion (14), and gastric emptying (15) and displays lipolytic effects (16). An inverse relationship between GLP-1 and ghrelin levels has been demonstrated after a standard glucose tolerance test in humans (17).…”
mentioning
confidence: 99%
“…GLP-1 has been shown to stimulate lypolysis in rat [102] and human [103] adipocytes. In a small study of 20 patients with type 2 diabetes, a continuous 6-week infusion of GLP-1 produced reductions in fasting and 8-hour mean concentrations of free fatty acids [104].…”
Section: Glp-1 Synthesis Secretion and Degradationmentioning
confidence: 99%
“…Treatment with GLP-1 at supraphysiologic concentrations resulted in increased femoral arterial blood flow correlated with whole- The beneficial effects of GLP-1 on CV parameters may also occur indirectly through GLP-1-mediated improvements in fatty free acid levels and glucose disposal. GLP-1 has been shown to stimulate lypolysis in rat [102] and human [103] adipocytes. In a small study of 20 patients with type 2 diabetes, a continuous 6-week infusion of GLP-1 produced reductions in fasting and 8-hour mean concentrations of free fatty acids [104].…”
mentioning
confidence: 99%